The Relationship Between Responsible Leadership and Organisational Commitment and the Mediating Effect of Employee Turnover Intentions: An Empirical Study with Australian Employees - Haque, Amlan (Journal of business ethics, 2019)
Contemporary leaders are increasingly challenged to execute their leadership roles with a higher sense of responsibility. However, only a handful of studies have empirically examined the influence of responsible leadership on employee and organisational outcomes. Using Social Identity Theory and Psychological Contract Theory, this paper reports the findings of the relationship between responsible leadership and organisational commitment through the mediating role of employee turnover intentions. A web-based online survey was administered to collect data targeting a sample of 200 Australian employees working full time. Structural equation modelling was used to analyse the data. The results reveal that perceived responsible leadership significantly influences employees’ organisational commitment and their turnover intentions. Moreover, the direct relationship between responsible leadership and organisational commitment was found to be partially mediated by employees’ turnover intentions.